Vegetable Garden at School - Serra, S.; Menezes, S.; Afonso, P.; Rosário, I.; Santos, J. (Open Schools Journal for Open Science, 2020)
This project began in 2018/2019 due to the interests shown by three classes of the 5th year. Through a brainstorm, we realized that the concern about the lack of green spaces was common to several students of the school. Thus, the vegetable garden would make the school greener and more open to the community. The space for construction was chosen and partnerships were created with the department of environmental management and transport of Odivelas (CMO), and the school parents association. We have privileged collaborative and interdisciplinary work to streamline various activities throughout the school year. The study of soil, seeds, autochthonous plants and pollinating insects was done with the help of class teachers and librarian teachers. The days of the native forest and the tree were celebrated with the planting of trees and the holding of a plant fair. At school and throughout the year students disseminated their project through informative posters, school radio and the school's website.